Investigation of a converter fault for a DFIG wind turbine and analysis of the resulting gearbox component loads. Issue 1 (1st April 2022) - Röder, Julian; Jacobs, Georg; Bosse, Dennis; Herzog, Fabian; Graf, Lukas
Abstract: Doubly fed induction generators are widely used in wind turbines in the field. The main advantage is the significantly lower cost of the partial scale power converter compared to the full scale power converter. Converter faults in wind turbines lead to significant generator torque excitations that lead to dynamic loads in the drivetrain. Dynamic loads and changing rotational speeds can lead to gearbox damages. The generator torque excitations have the highest influence on the high speed shaft torque due to the coupling to the generator. Gearbox damages occur mainly on the components of the high speed shaft. Thus, in this paper the influence of a converter fault in a wind turbine with doubly fed induction generator on the high speed shaft component damages is investigated. It is shown that the converter fault can induce dynamic torque excitations with a maximum increase to around 2.5 times rated torque. Due to the resulting dynamic gearbox loading the safety against scuffing in the high speed gear stage decreases by maximum 19 percent. The smearing risk in the high speed shaft bearings increases to around 2 times the value during rated power production.